Laryngoscopic characteristics related to the risk of cancerization of vocal cord leukoplakia. (2nd August 2021) - Li, Li-Juan; Yu, Zhan; Zhu, Ji-Qing; Wang, Mei-Ling; Li, Zhi-Xiang; Yang, Cong; Ni, Xiao-Guang
Abstract: Background: The diagnosis of vocal cord leukoplakia mainly relies on laryngoscopy. The morphology of vocal cord leukoplakia under laryngoscope is closely related to the pathological nature of leukoplakia. The specific manifestations associated with high-risk vocal cord leukoplakia remain to be explored. Objective: To investigate the characteristics of low-risk and high-risk vocal cord leukoplakia under conventional white light imaging (WLI) laryngoscopy and its correlations with narrow band imaging (NBI) laryngoscopy. Methods: One hundred and seventy-five cases of vocal cord leukoplakia were divided into low-risk and high-risk groups. The characteristics of low-risk and high-risk vocal cord leukoplakia under WLI laryngoscopy and its correlations with NBI laryngoscopy were analyzed. Results: Logistic regression analysis showed that thickness and hyperemia were independent factors ( p < .05). Hyperemia had a strong consistency with the visualization of spots under NBI laryngoscopy (kappa = 0.758). The sign of hyperemia and the NBI classification had equivalent diagnostic efficacy for predicting the risk of cancerization of vocal cord leukoplakia. Conclusion: The sign of hyperemia under WLI laryngoscopy is significantly correlated with the visualized spots under NBI laryngoscopy. Hyperemia is an important feature for predicting malignant potential of vocal cord leukoplakia.